Charisma: Religious Measurement - Olga G. Sladneva (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The problem of this work is the analysis of influence of charismatic persons on society through a religion prism. The purpose of the article is in judgment of relevance of religious sense of charisma today through not outdate communication with such existentials of human life as belief, hope and love. Methodology. The methodology of this work contains informative approaches: comparative, hermeneutical, dialectical and structuralist one. The scientific novelty. Novelty of this work is in communication research of the existentials of human life (belief, hope, love) and charisma. Charismatic persons as the elite are ideals in society. They are its driving forces as they have direct impact on the people. People, in their turn, need them as sources of belief, hope and love the set of which is a guarantee of happiness. Especially brightly this phenomenon is reflected in the religious sphere of life of society. Conclusions. It is revealed that the concept of charisma exists in other world religions and has common features. It is shown that the modern concept of charisma differs from the concept of "Christian" charisma. However, today as two thousand years ago, charismatics bear belief, hope and love in souls of their followers, making them happy.